2022
DOI: 10.46381/reic.v20i2.689
|View full text |Cite
|
Sign up to set email alerts
|

Excusas, justificaciones y experiencias. Los estresores en las narrativas de varones que ejercieron violencia de género

Abstract: Fundamentándose en la criminología narrativa y la Teoría de la Neutralización, el objetivo del presente artículo es analizar las circunstancias estresoras referidas por los varones que agredieron físicamente (letal y no letalmente) a sus parejas o exparejas mujeres y las justificaciones y/o excusas que vinculan a este hecho. Desde un enfoque cualitativo-hermenéutico, se analizó un corpus de 34 entrevistas proveniente de proyectos independientes en Argentina, España y Venezuela. Se identificaron cinco ejes de t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 36 publications
2
3
0
Order By: Relevance
“…Participants indicated that their “use of alcohol and/or drugs” was the main trigger for the violent event, attributing their behavior to the substance’s effect. This result is consistent with previous studies ( 19 , 27 ) that reveal men who assault their partners consider alcohol and/or drugs a stress factor that provokes their offense. However, it has been observed that this is a way to justify their lack of self-control and neutralize their responsibility for the acts in order to maintain a positive self-identity ( 19 ).…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Participants indicated that their “use of alcohol and/or drugs” was the main trigger for the violent event, attributing their behavior to the substance’s effect. This result is consistent with previous studies ( 19 , 27 ) that reveal men who assault their partners consider alcohol and/or drugs a stress factor that provokes their offense. However, it has been observed that this is a way to justify their lack of self-control and neutralize their responsibility for the acts in order to maintain a positive self-identity ( 19 ).…”
Section: Discussionsupporting
confidence: 93%
“…This result is consistent with previous studies ( 19 , 27 ) that reveal men who assault their partners consider alcohol and/or drugs a stress factor that provokes their offense. However, it has been observed that this is a way to justify their lack of self-control and neutralize their responsibility for the acts in order to maintain a positive self-identity ( 19 ). This result is also reaffirmed by various authors ( 13 17 ) who have demonstrated a close relationship between alcohol and/or drug use and GBV.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations